Identification of the Potential for Development of the Rainforest Lodges Kedah Ecotourism Area, Gayo Lues District, Aceh Province - Sulaiman, Sulaiman; Thoha, Achmad Siddik; Sulistiyono, Nurdin (MultiTech Publisher, 2024)
Aceh Province's natural resource wealth is diverse, offering natural panoramas, flora and fauna, and rainforest areas with attractive attractions for both domestic and foreign tourists. Forestry-based ecotourism has the potential to become a leading sector in the tourism industry. This research aims to map potential attractions, amenities, and regional accessibility of the Rainforest Lodges Kedah ecotourism area in Gayo Regency Lues Aceh Province. The area has unique natural resources, including beautiful flora and fauna, clear river flow, and tourist activities such as nature viewing, facilities, research/education, and sports. The area can accommodate up to 1,642 people per day. The ecotourism development strategy is in the quadrant one (I) SWOT matrix, allowing for optimal utilization of existing opportunities and support for aggressive growth